PREPARAÇÃO, CARACTERIZAÇÃO E AVALIAÇÃO DA ESTABILIDADE E BIOCOMPATIBILIDADE IN VITRO DE NANOCÁPSULAS CONTENDO ATRA - Homrich, Shayenne Scheffer (2021)
Among the different types of acute myeloid leukemia (AML), one of the specific subtypes is Acute Promyelocytic Leukemia (APL). There, there is an accumulation of abnormal promyelocytes in the bone marrow and/or peripheral blood, a scenario that causes the risk of thrombotic and hemorrhagic complications. This leukemia subtype has a specific drug for its treatment, all-trans-retinoic acid (ATRA). ATRA is a natural metabolite derived from retinol, belongs to the class of retinoids, and can act on the bone marrow as a cell differentiation therapy, where cell pro-apoptosis is facilitated, and the growth of leukemic cells is inhibited. However, despite the effectiveness of treatment with ATRA, some patients develop a severe reaction to the drug, known as LPA differentiation syndrome, which is considered very serious and has considerable lethality rates. Several studies have been developed to reduce these disadvantages and effects of ATRA, through different delivery systems, such as, for example, nanocapsules, which when together with the drug, improve solubility, photosensitivity, toxicity, chemical stability, bioavailability, and/or efficacy. Several successes were achieved in the work, among them the main one was that the cytotoxicity of this antineoplastic agent was reversed after it was nano encapsulated when compared to its free form. The results for the coagulation cascade showed that the two lowest concentrations present a safe profile, without altering the intrinsic and extrinsic pathways. The results of molecular docking suggest (for in vitro and in vivo tests) that the best interactions that ATRA can do are with the inflammatory proteins TNF-α, CATH-G, thrombin, and fibrinogen. it is worth highlighting the good perspectives regarding the intravenous administration of nanoparticles containing ATRA.